2020
DOI: 10.2147/cmar.s254784
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Natural Product Fucoidan Inhibits Proliferation and Induces Apoptosis of Human Ovarian Cancer Cells: Focus on the PI3K/Akt Signaling Pathway</p>

Abstract: Objective: Ovarian cancer (OC) is the leading cause of death among gynecological tumors; however, no effective treatment is currently available. Fucoidan, which is extracted from marine algae, has significant anti-cancer effects. The aim of this study was to determine the effects of fucoidan on the proliferation and apoptosis of OC cells through inhibition of the PI3K/Akt signaling pathway. Methods: Human ovarian normal epithelial cells (IOSE80) and human OC cells (SKOV-3, A2780, OVCAR-3, TOV-112D, and Caov-3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…In the acute promyelocytic leukemia cell line incubated with fucoidan resulted in cell cycle arrest in the G1 phase (Atashrazm et al, 2016). The same trend of the result was also demonstrated in HT29 colorectal cancer cells, MCF-7 breast cancer cells, and human ovarian cancer cells with downregulation of cyclin D1 and CDK4 (Banafa et al, 2013;Han et al, 2015;Liu et al, 2020). In the present study, we found that treatment with fucoidan in CL-6 cells resulted in cell cycle arrest in the G0/G1 phase.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the acute promyelocytic leukemia cell line incubated with fucoidan resulted in cell cycle arrest in the G1 phase (Atashrazm et al, 2016). The same trend of the result was also demonstrated in HT29 colorectal cancer cells, MCF-7 breast cancer cells, and human ovarian cancer cells with downregulation of cyclin D1 and CDK4 (Banafa et al, 2013;Han et al, 2015;Liu et al, 2020). In the present study, we found that treatment with fucoidan in CL-6 cells resulted in cell cycle arrest in the G0/G1 phase.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, Western blot analysis revealed the decreased expression levels of cyclin D1 and CDK4. The suppression of the PI3K/Akt signaling pathway by fucoidan results in the decreased expression levels of cyclin D1 and CDK4 which induce cell cycle arrest in the G0/G1 phase as described by a recent study (Liu et al, 2020) In conclusion, the results presented in this study revealed that fucoidan could exert cytotoxicity in CL-6 cholangiocarcinoma via the induction of apoptosis and cell cycle arrest. Nevertheless, future research about the anticancer effect of fucoidan against cholangiocarcinoma should be investigated in other signaling pathways related to its critical characteristics such as migration, invasion, and angiogenesis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…At a concentration of 1.0 mg/mL, fucoidan derived from C. okamuranus increased the G0/G1-phase population fraction of Huh7 hepatocarcinoma cells. This mechanism was followed by a decrease in the S-phase fraction, suggesting that fucoidan may cause cell cycle arrest in the G0/G1 phase [ 53 ]. Zhang et al demonstrated that when high-molecular-weight fucoidan was extracted from Cladosiphon novae-caledoniae kylin and then digested with glysidases, it produced LMWF.…”
Section: Anticancer Potential Of Fucoidan: Insights From Recent Studiesmentioning
confidence: 99%
“…As a natural polysaccharide extracted from brown algae, fucoidan was proved to have many biological effects (12)(13)(14)(15)(16). The anti-tumor abilities of fucoidan were confirmed in pancreatic cancer, bladder cancer, ovarian cancer and other types of cancers (65)(66)(67)(68). Fucoidan could inhibit the occurrence and development of tumor by regulating tumor immunity (21,22), inhibiting angiogenesis (23), interfering with cell cycle and apoptosis (19,20), which is considered to have a broad prospect in the field of tumor therapy.…”
Section: Discussionmentioning
confidence: 99%